YTHDF3 Is Involved in the Diapause Process of Bivoltine Bombyx mori Strains by Regulating the Expression of Cyp307a1 and Cyp18a1 Genes in the Ecdysone Synthesis Pathway - Yanhua Chen; Bingyan Fan; Ayinuer Yasen; Juan Zhu; Meixian Wang; Xingjia Shen (Biomolecules, 2022)
The variable diapause features of bivoltine silkworm (Bombyx mori) strains regulated by environmental signals in the embryonic stage are closely related to epigenetics. Previously, we showed that the expression of YTHDF3 is significantly different in the pupae of the bivoltine silkworm Qiufeng developed from eggs incubated at a normal temperature (QFHT, diapause egg producer) compared to those from eggs incubated at a low temperature (QFLT, nondiapause egg producer), indicating that the expression of diapause-associated genes is regulated by the m6A modification level. However, how YTHDF3 regulates the expression of diapause-related genes remains unclear. In this study, we observed that the knockdown of B. mori YTHDF3 resulted in delayed embryo development, while the overexpression of YTHDF3 resulted in the transformation of nondiapause-destined eggs into a mixture of diapause and nondiapause eggs. Further studies showed that YTHDF3, as a reading protein, can recognize the m6A site of Cyp307a1 and Cyp18a1 genes in the ecdysone synthesis pathway (ESP), and the overexpression of YTHDF3 affects the diapause traits of the silkworm by decreasing the stabilities of mRNAs of Cyp307a1 and Cyp18a1 and inhibiting their translation. The above results demonstrate that m6A modification mediates YTHDF3 to affect the expression levels of its target genes, Cyp307a1 and Cyp18a1, in the ESP to regulate diapause in bivoltine B. mori. This is the first report of the m6A methylation regulation mechanism in diapause in B. mori and provides new experimental data for clarifying the diapause regulation network.